STUDY OF THE INCIDENCE OF SKIN DISEASES AMONG CHILDREN IN ISFAHAN REGION - A.H. Momtaz; M. Moshtaghi; M. Ghadiry (Tehran University of Medical Sciences, 1975)
The purpose of this study was to investigate the incidence of different types of skin diseases among 657 children who were seen during one year period (Oct. 1971-Setp. 1972) at the skin clinics of the Isfahan University hospital. The incidence of different types of skin disease was compared with those of the adults. In general this study shows that in Isfahan area the incidence of skin infection among children were relatively higher than other skin disorder. Since the incidence of skin infections can be assumed to reflect the general health situation of the community, the improvement of socio-economic, environmental situation as well as the provision of medical care in the community could lead towards the reduction of the occurrence of skin infection.